2014
DOI: 10.1212/wnl.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

Proximal nerve magnetization transfer MRI relates to disability in Charcot-Marie-Tooth diseases

Abstract: Objective: The objectives of this study were (1) to develop a novel magnetization transfer ratio (MTR) MRI assay of the proximal sciatic nerve (SN), which is inaccessible via current tools for assessing peripheral nerves, and (2) to evaluate the resulting MTR values as a potential biomarker of myelin content changes in patients with Charcot-Marie-Tooth (CMT) diseases.Methods: MTR was measured in the SN of patients with CMT type 1A (CMT1A, n 5 10), CMT type 2A (CMT2A, n 5 3), hereditary neuropathy with liabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
89
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(102 citation statements)
references
References 43 publications
9
89
2
2
Order By: Relevance
“…The sciatic nerve is labelled with the red oval. The sciatic nerve diameter of the patient (mean ± SEM = 4.3 ± 0.1 mm) was reduced relative to previously published values in controls (mean ± SD = 5.1 ± 0.6) . (b) Corresponding magnetic transfer ratio ( MTR ) map from the same slice.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The sciatic nerve is labelled with the red oval. The sciatic nerve diameter of the patient (mean ± SEM = 4.3 ± 0.1 mm) was reduced relative to previously published values in controls (mean ± SD = 5.1 ± 0.6) . (b) Corresponding magnetic transfer ratio ( MTR ) map from the same slice.…”
Section: Resultsmentioning
confidence: 77%
“…(c) Mean MTR values versus age for controls and the patient with CMTX 4. Note that MTR values were not dependent on age in controls (•) (mean ± SD = 37.2 ± 2.3) and MTR values in the patient with CMTX 4 () (mean ± SEM = 33.4 ± 0.3 p.u.) were in the lower range of values observed in controls.…”
Section: Resultsmentioning
confidence: 95%
“…First, the CSMT method was tested using oil/agar phantoms, though one animal model study was performed to demonstrate feasibility of the method. However, for in vivo applications, particularly in clinical settings, multiple confounding factors, including B 0 and B 1 inhomogeneity , T 1 effects , eddy current effects , and susceptibility‐induced fat‐resonance shifts , need to be considered. The effect of B 0 inhomogeneity, as one of the potential limitations of the current method, should be included in the model, particularly for potential applications to abdominal imaging of visceral organs.…”
Section: Discussionmentioning
confidence: 99%
“…The fluid sensitivity of MRI provides detection of edema in nerves potentially caused by various pathologic mechanisms including inflammation, ischemia, and autoimmune disease . Quantitative mapping of diffusion, T2, and magnetization transfer demonstrated promising results in monitoring nerve degeneration …”
mentioning
confidence: 99%
“…14,15 Quantitative mapping of diffusion, T2, and magnetization transfer demonstrated promising results in monitoring nerve degeneration. 9,16,17 MRI evaluation of nerve fascicular structures, however, has not been reliable because of the limited resolution on the widely used 1.5T or 3T MRI scanners. High-resolution ultrasound imaging showed that evaluation of nerve fascicles could improve preoperative planning 18 or identification of nerve pathology.…”
mentioning
confidence: 99%